2020
DOI: 10.35848/1347-4065/aba157
|View full text |Cite
|
Sign up to set email alerts
|

Pilot demonstration of correlation-domain distributed temperature sensing using forward Brillouin scattering

Abstract: Forward Brillouin scattering (FBS) has been regarded as a key tool for distributed sensing of strain, temperature, acoustic impedance, etc. To date, FBS-based distributed sensing has been experimentally reported only by time-domain techniques. In this paper, we demonstrate correlation-domain distributed temperature sensing using cascaded FBS seeded by backward stimulated Brillouin scattering (SBS). By localizing the backward SBS using synthesized optical coherence function, cascaded FBS can also be localized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We showed that this configuration can effectively mitigate such systematic errors, except for the cases where the intrinsic BFS is asymmetrically distributed outside the strained section. Compared to the injection-locking technique previously reported for BOCDA [20], our method can be easily implemented and is more compatible with BOCDR than BOCDA. However, we need to admit that this configuration spoils one of the most important merits of BOCDR, i.e., single-end accessibility.…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that this configuration can effectively mitigate such systematic errors, except for the cases where the intrinsic BFS is asymmetrically distributed outside the strained section. Compared to the injection-locking technique previously reported for BOCDA [20], our method can be easily implemented and is more compatible with BOCDR than BOCDA. However, we need to admit that this configuration spoils one of the most important merits of BOCDR, i.e., single-end accessibility.…”
Section: (B)mentioning
confidence: 99%
“…By sweeping the modulation frequency, the position of the correlation peak can be scanned along the FUT, and the distributed information of the Brillouin gain spectrum (BGS) and/or the Brillouin frequency shift (BFS) can be obtained. In most of the BOCDA and BOCDR systems reported so far [15][16][17][18][19][20][21][22][23] (with a small number of exceptions [24][25][26]), a direct modulation scheme, in which the laser driving current was directly modulated to achieve optical frequency modulation (FM), was employed because of its simplicity and cost efficiency. However, the direct modulation scheme suffers from inevitable amplitude modulation (AM), which sometimes deteriorates the system performance such as spatial resolution [27,28].…”
mentioning
confidence: 99%
“…Because of the cross-sensitivity of acoustic signals, these measurement methods are of limited efficacy in complex spaces. Optical fibers can be arranged in complex spatial structures and can resist electromagnetic interference, so their usage has received extensive attention [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] FBS can also be utilized to achieve fiber optic temperature or strain measurements. [5][6][7][8][9][10] Different from backward stimulated Brillouin scattering (BSBS) caused by longitudinal acoustic modes, FBS is induced by transverse modes, which are radial acoustic modes (R 0,m ) and torsional-radial modes (TR 2,m ). The fact that FBS occurs by the transverse acoustic waves enables the FBS effect to be applied to acoustic impedance sensing.…”
mentioning
confidence: 99%
“…In this letter, we present our findings that the frequency shift dependencies of R 0,m induced FBS spectra on acoustic impedance are different with different R 0,m modes in large effective area fiber (LEAF), which are similar to their frequency shift dependencies on temperature. 5,6,8,10) Then using two R 0,m modes that would achieve the minimum measurement error, we implement discriminative measurement of temperature and acoustic impedance.…”
mentioning
confidence: 99%